Whole-university approaches to embedding well-being in the curriculum: a scoping review - Bannigan, Gráinne; McGrath, Denise; Matthews, James (Frontiers in Education, 2025)
Increasingly lower levels of well-being are reported by university students, and higher education (HE) services are unable to cope. Issues persist relating to the conceptualization and definition of well-being. There is a lack of clarity around what it means for something to be “embedded in the curriculum,” and how this aligns with a whole-university approach toward supporting student well-being. It is important to understand how this may have affected the design, delivery, and efficacy of such efforts to embed well-being in the HE curriculum in recent years. The objective of this review was to scope out the breadth of literature on the topic of embedding well-being in the curriculum to support HE students, specifically from the perspective of an integrated, whole-university approach. A total of 72 published and grey literature articles and documents were included for analysis. Findings are reported on the key characteristics of embedded well-being approaches, how these are underpinned by theory and rationale, how key concepts are defined and understood, who the key actors are, and what the main outcomes of these approaches are.Systematic review registrationA scoping review protocol was registered with Open Science Framework https://doi.org/10.17605/OSF.IO/9BVQY.